Differential antiviral activity of Porphyridium cruentum polysaccharides against VHSV and NNV infections - Parra-Riofrio, Geovanna; Moreno-García, Patricia; Abdala-Díaz, Roberto Teófilo; García-Rosado, Esther; Uribe-Tapia, Eduardo; Alonso-Sánchez, María del Carmen; Béjar-Alvarado, Julia (My University, 2021)
The use of functional food can be an interesting approach to prevent viral diseases in aquaculture facilities. An increasing number of studies have suggested that marine microorganisms can be a relevant source of substances with a putative use in preventing viral diseases. In particular, the antiviral activity of polysaccharides has been widely described against infections affecting higher vertebrates. In this study, we evaluate the antiviral activity of Porphyridium cruentum polysaccharides against two fish viruses: VHSV and NNV. Two different approaches have been used: (i) treatment of cells with polysaccharides before virus inoculation and (ii) addition of polysaccharides on cells after viral inoculation. Viral multiplication in treated and non-treated cells has been measured by viral genome quantification at different times post infection (p.i.). The anti-VHSV activity of P. cruentum polysaccharides has been demonstrated, blocking viral adsorption to cellular receptor, and preventing intracellular viral replication. On the contrary, no anti-NNV activity has been detected.
Keywords: Polisacáridos; Antivirales; Porphyridium cruentum; VHSV; NNV; Polysaccharides; Antiviral activity